Advanced Graph Database Strategies: AI-Driven Migration and Security for Complex Relationships - Tandra, Achyut Kumar Sharma (International Journal of Computing and Engineering, 2025)
This article examines how graph database models address the fundamental drawbacks of traditional relational databases when handling highly interconnected datasets. By structuring data as nodes and relationships rather than tables that require expensive join operations, graph databases enable the rapid traversal and querying of complex relationship patterns. The article explores the theoretical foundations, architectural components, and performance characteristics that make graph databases particularly well-suited for applications in social networks, fraud detection, recommendation systems, and supply chain optimization. The article highlights AI-powered migration frameworks that facilitate the transition from relational to graph models through automated schema analysis and transformation techniques. Through diverse implementation case studies, the article demonstrates how organizations across industries leverage graph databases to unlock previously inaccessible insights from their relationship-centric data. The article also addresses critical considerations in security governance, including relationship-level access controls and privacy protections specific to graph structures. Looking toward future developments, the article discusses emerging integration opportunities with technologies like digital twins and quantum computing that promise to enhance graph database capabilities further. This article establishes graph database technology as an alternative to relational systems and a transformative approach to managing interconnected data, enabling organizations to extract maximum value from their relationship patterns.